Colo-rectal endoscopic full-thickness resection (EFTR) with the over-the-scope device (FTRD®): A multicenter Italian experience. Issue 3 (March 2019) - Andrisani, G.; Soriani, P.; Manno, M.; Pizzicannella, M.; Pugliese, F.; Mutignani, M.; Naspetti, R.; Petruzziello, L.; Iacopini, F.; Grossi, C.; Lagoussis, P.; Vavassori, S.; et al.
Abstract: Background and aim: Endoscopic full-thickness resection(EFTR) with FTRD ® in colo-rectum may be useful for several indications.The aim was to assess its efficacy and safety. Material and methods: In this retrospective multicenter study 114 patients were screened; 110 (61M/49F, mean age 68 ± 11 years, range 20–90) underwent EFTR using FTRD ® . Indications were:residual/recurrent adenoma (39), incomplete resection at histology (R1 resection) (26), non-lifting lesion (12), adenoma involving the appendix (2) or diverticulum (2), subepithelial lesions(10), suspected T1 carcinoma (16), diagnostic resection (3). Technical success (TS: lesion reached and resected), R0 resection (negative lateral and deep margins), EFTR rate(all layers documented in the specimen) and safety have been evaluated. Results: TS was achieved in 94.4% of cases. EFTR was achieved in 91% with lateral and deep R0 resection in 90% and 92%. Mean size of specimens was 20 mm (range 6–42). In residual/recurrent adenomas, final analysis revealed: low-risk T1 (11), adenoma with low-grade dysplasia (LGD) (24) and high-grade dysplasia (HGD) (3), scar tissue (1). Histology reports of R1 resections were: adenoma with LGD (6), with HGD (1), low-risk (6) and high-risk (1) T1, scar tissue (12). Non-lifting lesions were diagnosed as: adenoma with HGD (3), low-risk (7) and high risk (2) T1. Adverse clinical events occurred in 12 patients (11%), while adverse technical events in11%. Three-months follow-up was available in 100 cases and residual disease was evident in only seven patients. Conclusions: EFTR using FTRD ® seems to be a feasible, effective and safe technique for treating selected colo-rectal lesions. Comparative prospective studies are needed to confirm these promising results.